A new didolodontid mammal from the late Paleocene–earliest Eocene of Laguna Umayo, Peru - Gelfo, Javier Nicolás (2011)
A previously undescribed tooth from the Muani Formation at the Laguna Umayo locality, Peru, represents the new didolodontid Umayodus raimondi gen. et sp. nov., here diagnosed by the presence of a well developed metastylid and ectostylid, and a twinned hypoconulid. This taxon is closely related to the middle Paleocene genera Escribania and Raulvaccia from the locality of Punta Peligro in Patagonia, Argentina. Phylogenetic analysis here performed indicates that they constitute a monophyletic group within Didolodontidae, supported by five derived characters: the hypocone well developed and close to the protocone; the strongly concave precingulum; the contact between the postcristid and the entoconid; the contact of the crista pre-paraconular, precingulum and parastyle; and the mesiodistal enlargement of the m3 talonid. Their paleogeographic distribution fit with those of the actual Andean Region of the Austral Kingdom. The previously assumed ThanetianYpresian age assignment for the Laguna Umayo LU3 fauna is here reinforced by faunistic comparisons with the earliest Eocene Murgon fauna, in Australia, and the Itaboraian South American Land Mammal Age, represented from faunas of Patagonia, Argentina and So Jos de Itabora, Brazil.